Multidisciplinary management of interstitial lung diseases: A real-life study - Biglia, Caroline; Ghaye, Benoît; Reychler, Gregory; Koenig, Sandra; Yildiz, Halil; Lacroix, Valérie; Tamirou, Farah; Hoton, Delphine; Pieters, Thierry; Froidure, Antoine (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: The guidelines on idiopathic pulmonary fibrosis (IPF) diagnosis established the crucial role of multidisciplinary discussion (MDD) in the diagnosis of interstitial lung diseases (ILD). However, real-life evaluation of MDD remains scarce. Our aim was to study the impact of a well-structured MDD on etiological assessment, diagnosis, and management of ILD. Methods: We collected and analysed all relevant data on patients concerning diagnosis and treatment before and after MDD during the year 2017. Results: One hundred fifty patients were included in the analysis. MDD had a significant impact on management: 42% of diagnoses were revised and the number of unclassifiable ILD was significantly reduced. Lung biopsy was performed in 26 patients (12 cryobiopsies and 14 surgical biopsies). The most prevalent diagnoses were connective-tissue disease associated ILD (32%), idiopathic pulmonary fibrosis (23%), hypersensitivity pneumonitis (13%) and granulomatous ILD (7%). MDD led to a change or initiation of treatment in 55% of cases. Nine patients were evaluated for transplantation, 23 patients were screened for academic or sponsored clinical trials and an 8-fold increase in rehabilitation inclusion was observed. Conclusion: Our results confirm the benefits of MDD on ILD management and diagnosis. MDD also facilitates access to non-pharmacological therapies and clinical trials.